Linguistic and Stylistic Means for Expressing Ethnocultural Heterostereotypes in Serbian Electronic Media - Spasić, Jelena Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper presents the analysis of the most frequent linguistic and stylistic means for expressing ethnocultural heterostereotypes in Serbian electronic media. The analysis has been conducted on concrete linguistic excerpts from Serbian electronic media. The paper aims to show characteristics of linguistic and stylistic means for expressing ethnocultural heterostereotypes. The research is a contribution to journalism stylistics. The most frequent linguistic means of ethnocultural heterostereotypes in Serbian electronic media are phraseology with ethnics and metaphors. The analysis of newspaper texts in Serbian digital media showed common choices of phraseology as expressive linguistic means, used to attract and sustain attention. The use of phraseology with ethnics makes factual newspaper text more expressible and draws attention, which also has an impact on shaping ethnocultural stereotypes among readers. In reports and columns, which belong to the publicistic genre, journalists use linguistic and stylistic means for expressing ethnocultural heterotereotypes not to reinforce stereotypes, but to encourage readers to rethink established ideas about other ethnocultural communities.
Keywords: stylistics; linguistics; electronic media; stereotypes; ethnostereotypes